1954
DOI: 10.1002/jps.3030430618
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Gum Turpentines of Pines*

Abstract: contained some a-pinene and the tails contained A3-carene. A heart cut (22%) had the following properties: b760, 165-166"; d:4, 0.8609; n ' : . ' , 1.4772; [a]"D4, -16.2". I-p-Pinene was identified in this fraction by preparation of nopinic acid melting a t 126". No depression in melting point occurred upon admixture with authentic nopinic acid.Fraction 7 was a mixture of 8-pinene and A3carene. Fraction 8 was mainly A3-carene. The nitrosate of Fraction 8 was prepared and after 3 recrystallizations melted a t 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

1966
1966
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 2 publications
1
22
1
2
Order By: Relevance
“…Our results are inconsistent with those of Pitman (197 I) who demonstrated that apinene was more effective than myrcene in attracting D. ponderosae in stands of western white pine and are surprising since a-pinene is the most common monoterpene in the resin of western white pine, which has low amounts of myrcene (Mirov 1961). The relative proportion of myrcene is higher in the resin of' lodgepole and ponderosa pines with amounts of myrcene greater than or equal to amounts of a-pinene (Mirov 196 1;Shrimpton 1973).…”
Section: Mean (+Se) Number Of Beetlescontrasting
confidence: 99%
“…Our results are inconsistent with those of Pitman (197 I) who demonstrated that apinene was more effective than myrcene in attracting D. ponderosae in stands of western white pine and are surprising since a-pinene is the most common monoterpene in the resin of western white pine, which has low amounts of myrcene (Mirov 1961). The relative proportion of myrcene is higher in the resin of' lodgepole and ponderosa pines with amounts of myrcene greater than or equal to amounts of a-pinene (Mirov 196 1;Shrimpton 1973).…”
Section: Mean (+Se) Number Of Beetlescontrasting
confidence: 99%
“…For example, one or more of the nonhost species sampled contained volatiles identified in the resin of host pines of D. frontalis (including the aggregation synergist α-pinene) as well as D. frontalis pheromone components (trans-verbenol and verbenone) (Mirov, 1961; A. rubrum C. alba L. styraciflua N. sylvatica P. serotina Q. falcata Q. marilandica Q. nigra…”
Section: Discussionmentioning
confidence: 99%
“…pini that is responsive only to one of two possible enantiomers (chemicals that cannot be structurally superimposed but otherwise are identical, see a-pinene in Figure 5.4); (2) a pheromone-sensitive type that is also responsive to some other synergists or inhibitors such as the frontalin cells of D. frontalis (the cells have at least two acceptor types each specific for one enantiomer of frontalin, see identical except that they are non-superimposable (mirror images). Carnphene, P-pinene, 3-carene, P-phellandrene, and limonene also have two enantiomers, although only (-)-P-pinene and (+)-3-carene are found in trees (Mirov, 1961). Myrcene and terpinolene are achiral.…”
Section: Sensory Organsmentioning
confidence: 99%